Method for efficiently preparing A-site Ba-containing proton conductor electrolyte by precursor combustion method

By combining precursor combustion method with flame combustion synthesis method and sol-gel technology, BCY, BZY, BZCY or BZCYYb electrolyte powders efficiently and densely sintered at 1300°C, solving the problems of Ba element volatility and grain boundary hyperplasia in high-temperature sintering. Improved SOFC performance and commercial application potential.

CN119219056APending Publication Date: 2024-12-31SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411247692.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the sintering of existing proton conductor electrolytes, Ba element volatilization and the anode support loses catalytic activity, resulting in a decrease in SOFC performance. The high sintering temperature increases grain boundary density and hinders proton transmission, limiting the commercial application of SOFC.

Method used

Precursor combustion method is adopted, combined with flame combustion synthesis method and traditional sol-gel method, by controlling the chemical ratio and combustion conditions of the precursor, it can effectively densely sinter BCY, BZY, BZCY or BZCYYb electrolyte powder at 1300℃ to avoid Ba element volatility and grain boundary hyperplasia in high temperature sintering.

Benefits of technology

It significantly reduces the sintering temperature, improves the chemical stability and structural integrity of the electrolyte, enhances the efficient transmission of protons, improves the overall performance of fuel cells, and simplifies the production process, reducing costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219056A_ABST
    Figure CN119219056A_ABST
Patent Text Reader

Abstract

The invention relates to a method for efficiently preparing an A-site Ba-containing proton conductor electrolyte by using a precursor combustion method, which innovatively adopts a technology for preparing electrolyte powder by using the precursor combustion method, is coupled with a flame synthesis technology and a sol-gel technology, and comprises the following steps: weighing raw materials according to the stoichiometric ratio of the proton conductor electrolyte, preparing precursor liquid, and preparing the A-site Ba-containing proton conductor electrolyte; adjusting the pH value of the precursor liquid, controlling the combustion condition, heating and drying the precursor liquid, combusting the obtained powder, and calcining at high temperature to form a corresponding crystal structure. Compared with the prior art, the preparation method has the advantages that the BCY, BZY, BZCY or BZCYYb electrolyte powder which is smaller and more uniform in particle size and higher in sintering activity is successfully prepared by controlling the chemical proportion and combustion conditions of the precursor. The electrolyte powder can be sintered to be compact at 1300 DEG C (the density is gt; and the temperature is far lower than 1600 DEG C required by the traditional method, so that the volatilization of Ba element in the high-temperature sintering and electrolyte densification processes is effectively avoided, and the battery performance and the sintering temperature are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid oxide fuel cell (SOFC) electrolyte powder preparation, and relates to a precursor combustion method for preparing a highly efficient sintered A-site Ba-containing proton conductor electrolyte. Background Art

[0002] One of the most pressing issues in today's society is the development of sustainable energy to address the environmental crisis caused by global warming and the exploitation of limited natural mineral resources. Advanced energy conversion and storage technologies, such as solid oxide fuel cells (SOFCs), have the characteristics of high energy conversion efficiency, low cost, and good long-term stability. SOFCs can use a variety of carbon-containing fossil fuels as fuels. During the energy conversion process, the fuel is not directly burned, which greatly improves the energy conversion efficiency and avoids or reduces the generation of toxic gases and pollutants such as dust. Its by-products are high-quality heat and water vapor. In the case of combined heat and power generation, the energy utilization rate can be as high as about 80%, which is clean and efficient.

[0003] Traditional oxygen ion conductor YSZ-based SOFC needs to work at high temperature (800℃–1000℃). High temperature places strict requirements on the chemical stability and thermal expansion matching of the battery structure, and makes it difficult to select the stack connector and sealing materials. High operating temperature also leads to high system cost, difficult hot and cold cycles, and poor long-term durability. These issues are key factors limiting the commercial application of SOFC. Currently, proton conductor electrolytes are receiving attention in the SOFC field. Proton conductor electrolytes can work effectively at lower operating temperatures (500℃-700℃), reducing the thermal management requirements and operating costs of SOFC systems. Currently, proton conductors used in SOFC include BaCe x Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY), BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb). Due to the poor sintering activity, these proton conductors need to be sintered at a high temperature of more than 1600°C to be fully dense. Too high a temperature will not only cause the Ba element to volatilize, but also cause the anode support to lose its catalytic activity. In addition, high-temperature sintering increases the grain boundary density, hindering proton transport. Therefore, in order to commercialize proton conductor SOFC, it is necessary to overcome the BaCex Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY) or BaZr x Ce y Y 1-x-y O 3-δ (BZCY) and BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb) The main obstacle of proton conductors is the high sintering temperature.

[0004] Patent CN117878366 A A multiphase proton conductor material, its preparation method and its application, belongs to the technical field of inorganic solid electrolyte materials. The invention provides a multiphase proton conductor material, which introduces a proton conductor electrolyte BZCY and a lithium ion electrolyte Li 6.4 La3Zr2Ta 0.6 O 12 (LLZTO), by mechanically mixing the two, sintering and densification can be achieved at a temperature not exceeding 1200°C. Although this technology can reduce the sintering temperature of multiphase proton conductor materials, the raw material preparation process is cumbersome and costly. In addition, the introduction of a large proportion of second phase materials will lead to thermal matching problems in the single cell structure, and compared with single phase materials, commercial promotion is lower. Patent CN118039988A A low-temperature solid oxide fuel cell electrolyte and a preparation method thereof and a medium- and low-temperature solid oxide fuel cell belong to the field of solid oxide fuel cell technology. The invention provides a method for preparing an electrolyte for a low-temperature solid oxide fuel cell, wherein an oxide powder, a dispersant and a solvent are ball-milled to obtain a mixed powder, and then a binder and a plasticizer are added for ball milling and vacuum degassing to obtain a slurry. Subsequently, a dense electrolyte can be obtained by coating, step sintering, and insulation at 1360°C. Although this technology can obtain a dense electrolyte at a sintering temperature of 1360°C, the purpose of this scheme is limited to the synthesis of oxygen ion conductors, and the preparation process requires multiple high-temperature calcinations, which has a negative impact on the thermodynamic stability of the materials of each component of the single cell. The process is complicated, time-consuming and labor-intensive.

[0005] With the further development of flame combustion synthesis technology, flame combustion synthesis technology has entered a new stage from laboratory preparation to industrial application. Flame combustion synthesis has the following advantages: high efficiency, the reaction time of the combustion synthesis method is very short, and the reaction can be completed in an instant, thereby greatly improving the reaction speed and efficiency. Compared with other preparation methods, the combustion synthesis method does not require precise experimental equipment and conditions, is very easy to experiment, and has strong controllability; the particle size, morphology and structure of nanomaterials can be regulated by adjusting factors such as the precursor ratio, reaction temperature and ion initial concentration of the reaction. The patent CN 103464064A discloses a system and method for synthesizing nanoparticles by swirl stagnant flame. The flame nanoparticle synthesis system has the characteristics of short burner structure and preparation process, uniform particle size and high purity. However, the swirl flame control device requires precise design and manufacturing process, resulting in a high overall cost of the system. In addition, the equipment needs to operate under high temperature and high pressure conditions, which is difficult to combine with other field technologies and has limited promotion.

[0006] Patent application CN201310499655.3 discloses a lithium carbonate / yttrium-doped barium cerium zirconate composite structure proton conductor material, with BaCe0.7Zr0.1Y0.2O3-δ (BCZY) as the matrix, and 2.5% lithium carbonate as the liquid phase sintering aid; prepared by soft chemical method: (1) using nitrate-citric acid gel self-combustion method to obtain light yellow BCZY powder; (2) using BCZY powder as the matrix material, adding lithium carbonate, ball milling and mixing, drying, grinding, sieving, dry pressing at 150MPa, and then calcining at 1200-1300℃, keeping warm for 5 hours, to obtain BCZY-2.5%Li2CO3 composite structure proton conductor material. The composite structure proton conductor material of the invention has good sintering and conductivity, and the conductivity at 700℃ reaches 10-2S / cm, which lays the foundation for the development of solid oxide fuel cells. However, for the performance of SOFC single cells, the introduction of a large proportion of Li elements will cause a decrease in the open circuit voltage, thereby reducing the power density of the single cell. Not only that, the sintering aid may react with other battery components, causing thermal matching problems with the single cell structure, resulting in performance degradation and reduced durability. In addition, the sintering aid will also cause abnormal growth or uneven structure of the proton conductor grains, affecting its mechanical strength and long-term stability as an electrolyte. Therefore, compared with single-phase materials, commercial promotion and engineering scalability are lower. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a method for efficiently preparing A-site Ba-containing proton conductor electrolyte by a precursor combustion method, and to couple the flame combustion synthesis method and the traditional sol-gel method to propose a method for utilizing precursor combustion to simply and quickly prepare BCY, BZY, BZCY or BZCYYb electrolyte powders that can be efficiently sintered in large quantities.

[0008] The object of the present invention can be achieved by the following technical scheme: a method for efficiently preparing a proton conductor electrolyte containing Ba at the A position by a precursor combustion method, wherein the proton conductor electrolyte comprises BaCe x Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY) or BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb) (any ratio of 0≤x+y+z≤1 can be used); the present invention successfully prepares BCY, BZY, BZCY or BZCYYb electrolyte powders with smaller and more uniform particle sizes by controlling the chemical ratio of the precursor and the combustion conditions. The method accurately weighs the raw materials according to the stoichiometric ratio of the proton conductor electrolyte, prepares the precursor liquid, adjusts the pH value of the precursor liquid, controls the combustion conditions to heat and dry the precursor liquid, and the obtained powder is burned and calcined at high temperature to form a corresponding crystal structure, which can achieve efficient and dense sintering of the electrolyte at 1300°C (density>99%), which is significantly lower than the traditional sintering temperature of 1600°C, and avoids the volatilization of the Ba element during the high-temperature sintering process.

[0009] Furthermore, the method comprises the following steps:

[0010] S1: Weigh the raw materials according to the stoichiometric ratio of the proton conductor electrolyte. The raw materials used are selected from Ba(NO3)2, Zr(NO3)4·5H2O, H8CeN8O according to the stoichiometric ratio of the proton conductor electrolyte. 18 , Y(NO3)3·6H2O, Yb(NO3)3·5H2O. Each raw material is H8CeN8O 18, Zr(NO3)4·5H2O, Ba(NO3)2, Y(NO3)3·6H2O, and Yb(NO3)3·5H2O are dissolved in distilled water in that order, and citric acid and ethylene glycol are added to the resulting solution. The amount of metal cations added is based on the metal cations in the raw materials used for the proton conductor electrolyte, so that the molar ratio of the metal cations to the ethylene glycol and citric acid is 1:1.5-2:1.5-2.

[0011] The pH value of the obtained solution is adjusted to 7-8 using ammonia water with a mass concentration of 15%-20% until the flocs in the solution disappear, and then the obtained mixed solution is placed in a constant temperature magnetic stirrer and stirred at a constant temperature of 40°C-60°C, and NH4NO3 and H2O2 solutions are added simultaneously. The amount of NH4NO3 and H2O2 solutions added is based on the proton conductor electrolyte, so that the molar ratio of the proton conductor electrolyte to the NH4NO3 and H2O2 solutions is 1: (10-15): (5-10).

[0012] The obtained solution is heated at 70°C-80°C with stirring for 8h-10h to obtain a precursor solution;

[0013] S2: The precursor solution obtained in S1 is transferred into an evaporating dish, and placed on an electric furnace to rapidly heat up at a heating power of 1000w-1500w, with continuous stirring. During this period, the water content of the precursor solution evaporates and dries into a porous solid material. The porous solid material is then placed in an insulating box filled with NO2. Under the action of the combustion aids NH4NO3, NO2 and H2O2, an exothermic reaction occurs rapidly, and finally all the black powder burns violently, and a phenomenon similar to tree branch growth occurs, while turning into white-yellow powder;

[0014] S3: The obtained white-yellow powder is crushed, kept at 1000-1200° C. for 5-7 hours and cooled with the furnace to obtain an electrolyte powder that can be sintered efficiently.

[0015] Further, H8CeN8O 18 As Ce source and combustion aid.

[0016] Furthermore, the mass concentration of the H2O2 solution is 60%-70%.

[0017] The present invention couples the flame combustion synthesis method and the traditional sol-gel method to propose a new process for preparing highly efficient sintered A-site Ba-containing proton conductor electrolyte powder by precursor combustion method. Compared with the traditional manufacturing method, the present invention successfully prepares BCY, BZY, BZCY or BZCYYb electrolyte powder with smaller and more uniform particle size by controlling the chemical ratio and combustion conditions of the precursor. The method can achieve efficient and dense sintering (density>99%) of the electrolyte at 1300°C by accurately weighing the raw materials, adjusting the pH value of the precursor liquid, controlling the combustion conditions and high-temperature calcination, which is significantly lower than the traditional sintering temperature of 1600°C, and avoids the volatilization of the Ba element during the high-temperature sintering process. Compared with the traditional preparation process, the present invention has the advantages of simple process, no need for external sintering aids, high production efficiency and easy industrial scale-up. It not only reduces the preparation cost, but also simplifies the production process of SOFC electrolyte powder, provides an effective solution for the densification of A-site Ba-containing proton conductor electrolyte, and also provides important technical support for the commercial development of SOFC.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The invention provides an innovative precursor combustion method for preparing electrolyte powders, coupling flame synthesis technology and sol-gel technology, which can achieve BaCe at a low temperature of 1300°C without relying on external sintering aids. x Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY) or BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb) Efficient sintering of electrolytes. This technology significantly improves the sintering activity of powders, reduces the chemical impurity problems that may be caused by high temperatures, simplifies production operations, effectively reduces energy consumption and production costs, and has significant industrial application value.

[0020] (2) In the present invention, the prepared Ba-containing proton conductor material can achieve densification at a lower sintering temperature, effectively suppressing the volatilization of Ba elements commonly seen in traditional high-temperature sintering processes, and significantly enhancing the chemical stability and structural integrity of the electrolyte material. In addition, appropriate temperature control helps to maintain the catalytic activity of the anode support and prevent excessive growth of grain boundaries. These optimization measures jointly promote the efficient transmission of protons and significantly improve the overall performance of the fuel cell.

[0021] (3) By controlling the chemical ratio of the precursor and the combustion conditions, the present invention can produce electrolyte powders with smaller particle size and more uniform distribution. This high sintering activity powder is not only suitable for traditional electrolyte film preparation technology, but also can meet the more stringent technical requirements of new electrolyte film, showing excellent cross-expandability and adaptability, and providing strong technical support for the commercialization of SOFC.

[0022] (4) The present invention provides a precursor combustion method for preparing highly efficient sintered BCY, BZY, BZCY or BZCYYb electrolyte powders, which does not rely on external sintering aids. The problem of difficult sintering of A-site Ba-containing proton conductor electrolytes is solved from the source of powder synthesis, and highly efficient sintering is achieved at a lower temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 BaZr was calcined at 1300°C for 6 hours using the precursor combustion method in Example 1. 0.2 Ce 0.7 Y 0.1 O 3-δ Electrolyte powder particle size distribution diagram;

[0024] Figure 2 In Example 2, BaZr was calcined at 1300°C for 6 hours using the precursor combustion method. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder particle size distribution diagram;

[0025] Figure 3 BaZr was calcined at 1300°C for 6 hours using the precursor combustion method in Example 1. 0.2 Ce 0.7 Y 0.1 O 3-δ SEM image of half-cell surface;

[0026] Figure 4 In Example 2, BaZr was calcined at 1300°C for 6 hours using the precursor combustion method. 0.1 Ce 0.7 Y 0.1 Yb0.1 O 3-δ SEM image of the half-cell surface. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The present invention couples the flame combustion synthesis method with the traditional sol-gel method to provide a method for preparing a highly efficient sintered A-site Ba-containing proton conductor electrolyte including BaCe x Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY) or BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb) powder precursor combustion method. The preparation steps include: accurately weighing raw materials, dissolving raw materials in sequence to prepare precursors, adjusting the pH value of precursor liquid, controlling combustion conditions, heating precursor liquid, powder combustion and high-temperature calcination to form corresponding crystal structures. The raw materials and equipment used in the present invention are all commonly used commercially available raw materials and equipment in this field.

[0029] The technical solution of the present application will be described in detail below with reference to the accompanying drawings.

[0030] Example 1

[0031] 1. BaZr 0.2 Ce 0.7 Y 0.1 O 3-δ Preparation of electrolyte powder:

[0032] S1: Weigh 261.34g (1mol) Ba(NO3)2, 85.86g (0.2mol) Zr(NO3)4·5H2O, 383.75g (0.7mol) H8CeN8O 18 , 38.30 g (0.1 mol) Y(NO3)3·6H2O and weigh 186.21 g (3 mol) ethylene glycol and 840.56 g (4 mol) citric acid in a molar ratio of metal cation to ethylene glycol to citric acid of 1:1.5:2;

[0033] S2: Press H8CeN8O 18, Zr(NO3)4·5H2O, Ba(NO3)2, and Y(NO3)3·6H2O were dissolved in 40 mL of distilled water in that order;

[0034] S3: Pour the nitrate solution obtained in S2 into 250 mL of citric acid solution, and then add ethylene glycol to the solution;

[0035] S4: adding 20% ​​ammonia water dropwise to the solution to adjust the pH value of the solution to 8 until the flocs in the solution disappear;

[0036] S5: placing the mixed solution obtained in step S4 into a constant temperature magnetic stirrer and heating it at a temperature of 60° C.

[0037] S6: According to the weighed BaZr 0.2 Ce 0.7 Y 0.1 O 3-δ Add 800 g NH4NO3 and 283.3 g H2O2 solution with a mass concentration of 60% to the mixed solution obtained in step S5 at a molar ratio of 1:10:5;

[0038] S7: Stir and heat the precursor solution obtained in S6 at 80° C. for 8 h;

[0039] S8: The precursor solution obtained in S7 is transferred into an evaporating dish, placed on an electric furnace and heated rapidly at a heating power of 1000w-1500w, with continuous stirring. During this period, the water in the precursor solution evaporates and dries into a porous solid material, which is then placed in an insulating box filled with NO2. Under the action of the combustion aids NH4NO3, NO2 and H2O2, the powder rapidly undergoes an exothermic reaction, and finally all the black powder undergoes violent combustion, a phenomenon similar to tree branch growth, and is transformed into a white-yellow powder;

[0040] S9: The white-yellow powder similar to branches is crushed, kept at 1100±10℃ for 6±0.1h and cooled with the furnace to obtain BaZr that can be sintered efficiently. 0.2 Ce 0.7 Y 0.1 O 3-δ Electrolyte powder.

[0041] 2. BaZr 0.2 Ce 0.7 Y 0.1 O 3-δ Preparation of Solid Oxide Fuel Cell Methods:

[0042] The single cell is prepared by the co-pressing method, and the specific steps are as follows:

[0043] (1) NiO and BaZr prepared in step (1)0.2 Ce 0.7 Y 0.1 O 3-δ The mixture was mixed in a mass ratio of 60:40, and then 10 wt.% of the total mass of the mixture was added with nano-graphite powder to obtain a composite anode powder. 0.30 g of the composite anode powder was weighed and poured into a tableting mold with a diameter of 12 mm to obtain a composite anode substrate; 0.09 g of BaZr 0.2 Ce 0.7 Y 0.1 O 3-δ After sieving, the powder is evenly spread on the composite anode substrate, uniaxially pressed for 60 seconds at a pressure of 100 MPa, and then demolded to obtain a half-cell embryo. The half-cell embryo is then calcined in an air atmosphere at 1300°C for 6 hours to sinter the electrolyte to obtain an anode-supported half-cell.

[0044] (2) BaZr prepared in step (1) 0.2 Ce 0.7 Y 0.1 O 3-δ Electrolyte powder and LCSF powder (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ , which can be a commercially available product or prepared by the method reported in existing literature. In this embodiment, reference document DOI:10.3390 / ma17040869 is prepared by sol-gel method) at a mass ratio of 7:3, and then mixed with pine alcohol and ethyl cellulose to prepare a composite cathode slurry (pine alcohol and ethyl cellulose are commonly used auxiliary materials in this field, and their amounts are added according to actual needs. In this embodiment, the composite cathode powder composed of electrolyte powder and LCSF powder is mixed with 6wt% ethyl cellulose-pine alcohol binder at a mass ratio of 1:1.5 to prepare a composite cathode slurry). The composite cathode slurry is evenly coated on the electrolyte side of the anode support half-cell and calcined in an air atmosphere at 1000°C for 1h to obtain BaZr prepared by the co-pressing method. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery.

[0045] Example 2

[0046] Step (1) Prepare BaZr as in Example 1 0.2 Ce 0.7 Y 0.1 O 3-δ Electrolyte powder is prepared by spin coating a single cell. The specific steps are as follows:

[0047] (1) NiO and BaZr 0.2 Ce0.7 Y 0.1 O 3-δ The mixture was mixed in a mass ratio of 60:40, and then 10 wt.% of the total mass of the mixture was added with nano-graphite powder to obtain a composite anode powder. 0.30 g of the composite anode powder was weighed and poured into a tableting mold with a diameter of 12 mm. The mixture was uniaxially pressed at a pressure of 100 MPa for 60 seconds, and the pressure was released and the mold was demolded to obtain the green embryo of the anode support. The anode support was then calcined in an air atmosphere at 1000 ° C for 2 hours to obtain the anode support;

[0048] (2) BaZr 0.2 Ce 0.7 Y 0.1 O 3-δ The electrolyte powder was mixed with pinene alcohol and ethyl cellulose to prepare an electrolyte slurry, which was coated on the anode support by a spin coater, and calcined in an air atmosphere at 1300°C for 6 hours to sinter the electrolyte to obtain an anode support half-cell. The cathode coating method was the same as in Example 1, and finally BaZr prepared by spin coating was obtained. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery.

[0049] Example 3

[0050] 1. BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Preparation of electrolyte powder:

[0051] S1: Weigh 261.34g (1mol) Ba(NO3)2, 42.93g (0.1mol) Zr(NO3)4·5H2O, 383.75g (0.7mol) H8CeN8O 18 , 38.30 g (0.1 mol) Y(NO3)3·6H2O and 44.91 g (0.1 mol) Yb(NO3)3·5H2O and weigh 186.21 g (3 mol) ethylene glycol and 840.56 g (4 mol) citric acid in a molar ratio of metal cation to ethylene glycol to citric acid of 1:1.5:2;

[0052] S2: Press H8CeN8O 18 , Zr(NO3)4·5H2O, Ba(NO3)2, Y(NO3)3·6H2O, and Yb(NO3)3·5H2O were dissolved in 40 mL of distilled water in that order;

[0053] S3: Pour the nitrate solution obtained in S2 into 250 mL of citric acid solution, and then add ethylene glycol to the solution;

[0054] S4: adding 20% ​​ammonia water dropwise to the solution to adjust the pH value of the solution to 8 until the flocs in the solution disappear;

[0055] S5: placing the mixed solution obtained in step S4 into a constant temperature magnetic stirrer at a heating temperature of 60°C;

[0056] S6: adding 800 g NH4NO3 and 283.3 g H2O2 solution with a mass concentration of 60% to the mixed solution obtained in step S5 according to the molar ratio of BZCYYb weighed 1:10:5;

[0057] S7: Stir and heat the precursor solution obtained in S6 at 80° C. for 8 h;

[0058] S8: The precursor solution obtained in S7 is transferred into an evaporating dish, placed on an electric furnace and heated rapidly at a heating power of 1000w-1500w, with continuous stirring. During this period, the water in the precursor solution evaporates and dries into a porous solid material, which is then placed in an insulating box filled with NO2. Under the action of the combustion aids NH4NO3, NO2 and H2O2, the powder rapidly undergoes an exothermic reaction, and finally all the black powder undergoes violent combustion, a phenomenon similar to tree branch growth, and is transformed into a white-yellow powder;

[0059] S9: The white-yellow powder similar to branches is crushed, kept at 1100±10℃ for 6±0.1h and cooled with the furnace to obtain BaZr that can be sintered efficiently. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder.

[0060] 2. BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The method for preparing a solid oxide fuel cell is to prepare the cell by a co-pressing method. The specific steps are as follows:

[0061] (1) NiO and BaZr prepared in step (1) 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mixture was mixed at a mass ratio of 60:40, and then 10 wt.% of the total mass of the mixture was added with nano-graphite powder to obtain a composite anode powder. 0.30 g of the composite anode powder was weighed and poured into a tableting mold with a diameter of 12 mm; 0.09 g of BaZr 0.1 Ce 0.7 Y0.1 Yb 0.1 O 3-δ After sieving, the powder is evenly spread on the composite anode substrate, uniaxially pressed for 60 seconds at a pressure of 100 MPa, and then demolded to obtain a half-cell embryo. The half-cell embryo is then calcined in an air atmosphere at 1300°C for 6 hours to sinter the electrolyte to obtain an anode-supported half-cell.

[0062] (2) BaZr prepared in step (1) 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder electrolyte powder and LCSF powder (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ ) was mixed with pine alcohol and ethyl cellulose in a mass ratio of 7:3 to prepare a composite cathode slurry. The composite cathode slurry was evenly coated on the electrolyte side of the anode support half-cell and calcined in an air atmosphere at 1000°C for 1h to obtain BaZr prepared by the co-pressing method. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery.

[0063] Example 4

[0064] Step (1) is the same as in Example 3 to obtain BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder, single cell is prepared by spin coating method, the specific steps are as follows:

[0065] (1) NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mixture was mixed in a mass ratio of 60:40, and then 10 wt.% of the total mass of the mixture was added with nano-graphite powder to obtain a composite anode powder. 0.30 g of the composite anode powder was weighed and poured into a tableting mold with a diameter of 12 mm. The mixture was uniaxially pressed at a pressure of 100 MPa for 60 seconds, and the pressure was released and the mold was demolded to obtain the green embryo of the anode support. The anode support was then calcined in an air atmosphere at 1000 ° C for 2 hours to obtain the anode support;

[0066] (2) BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δThe electrolyte powder was mixed with pinene alcohol and ethyl cellulose to prepare a slurry, which was coated on the anode support by a spin coater. After calcination at 1300°C in an air atmosphere for 6 hours, a half-cell was obtained. The cathode coating method was the same as in Example 3. Finally, BaZr prepared by spin coating was obtained. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery. Comparative Example 1

[0067] BaZr was synthesized by conventional solid phase method. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder and prepare anode support single cell. The specific steps include:

[0068] 1. BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Preparation of electrolyte powder

[0069] S1: Weigh 153.33 g (1 mol) of BaO, 12.32 g (0.1 mol) of ZrO2, 120.48 g (0.7 mol) of CeO2, 22.58 g (0.1 mol) of Y2O3 and 22.58 g (0.1 mol) of Yb2O3;

[0070] S2: BaO, ZrO2, CeO2, Y2O3 and Yb2O3 were mixed and added with 500 mL of anhydrous ethanol;

[0071] S3: The mixed solution obtained in S2 was placed in a ball mill and ball-milled at a speed of 400 rpm / min for 48 h;

[0072] S4: placing the mixed solution obtained in step S3 into a constant temperature oven for drying at a heating temperature of 40° C.;

[0073] S5: pouring the powder obtained in step S4 into a tablet pressing mold with a diameter of 12 mm; uniaxially pressing for 120 s at a pressure of 100 MPa, and releasing the pressure to obtain an electrolyte precursor green embryo;

[0074] S6: placing the electrolyte precursor embryo obtained in step S5 into a muffle furnace and keeping it at 1200° C. for 5 hours to obtain an electrolyte sheet;

[0075] S7: crushing and grinding the electrolyte sheet obtained in S6, and adding 500 mL of anhydrous ethanol to form a mixed solution;

[0076] S8: Repeat steps S2-S6 twice;

[0077] S9: The electrolyte sheet obtained in S8 is crushed to obtain BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder.

[0078] 2. BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Preparation of Solid Oxide Fuel Cell Methods:

[0079] Preparation of single cell by co-pressing method: composite anode powder is composed of NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio was 60:40, and then 10wt.% of nano graphite powder was added. 0.30g of composite anode powder was weighed and poured into a tableting mold with a diameter of 12mm; 0.09g of BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ After sieving, the powder is evenly spread on the composite anode substrate, uniaxially co-pressed at a pressure of 100 MPa for 60 seconds, and the pressure is released and demolded to obtain a half-cell embryo. The half-cell embryo is then calcined in an air atmosphere at 1600°C for 6 hours to sinter the electrolyte to obtain an anode-supported half-cell. The electrolyte powder and LCSF powder are mixed with pine alcohol and ethyl cellulose in a mass ratio of 7:3 to prepare a composite cathode slurry. The composite cathode slurry is evenly coated on the electrolyte side of the anode-supported half-cell and calcined in an air atmosphere at 1000°C for 1 hour to obtain BaZr prepared by the co-pressing method. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery.

[0080] Comparative Example 2

[0081] Step (1) Prepare BaZr in the same manner as in Comparative Example 1 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder, single cell is prepared by spin coating method, the specific steps are as follows: composite anode powder is composed of NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δThe composition is in a mass ratio of 60:40, and then 10wt.% of nano-graphite powder is added. 0.30g of the composite anode powder is weighed and poured into a tableting mold with a diameter of 12mm. The anode support is uniaxially pressed for 60s under a pressure of 100MPa, and the pressure is released and demolded to obtain the anode support embryo. Then, the anode support is calcined for 2h in an air atmosphere at 1000℃, and the electrolyte powder is mixed with pine alcohol and ethyl cellulose to prepare a slurry, which is applied to the anode support by a spin coater. The electrolyte is calcined for 6h in an air atmosphere at 1600℃ to sinter the electrolyte to obtain an anode support half-cell. The cathode coating method is the same as above, and finally BaZr prepared by spin coating is obtained. 0.2 Ce 0.7 Y 0.1 O 3-δ Single battery.

[0082] The powders obtained in Examples 1-4 were subjected to particle size analysis, the half-cells were observed for morphology using SEM, and the single cells obtained in Examples 1-4 and Comparative Examples 1-2 were subjected to electrochemical performance tests. The specific performance test methods are as follows:

[0083] (1) Power density of a single cell: measured using the two-terminal method. Apply silver paste evenly on the cathode side, place the electrolyte sheet to be tested in a box furnace, heat it to 400°C at 3°C ​​per minute in air, keep it warm for 2 hours, then turn off the furnace and cool it to room temperature. Use conductive silver paste to fix Φ0.2mm silver wire to the two surfaces of the sample to prepare a two-electrode system, which is then connected and fixed to the electrode wire of the electrochemical workstation. Use an electrochemical workstation to measure the current-power density (IP) curve of the single cell.

[0084] The test conditions are as follows: the fuel gas is humidified pure hydrogen (H2 flow rate is adjusted to 40 mL / min), the cathode side of the single cell is in contact with the air, and the test temperature is 700°C.

[0085] The test results are:

[0086] Open circuit voltage Power density Example 1 1.04V 0.92W Example 2 1.07V 1.02W Example 3 1.05V 1.05W Example 4 1.08V 1.19W Comparative Example 1 0.85V 0.53W Comparative Example 2 0.84V 0.68W

[0087] from Figure 1-2 It can be seen that the BaZr prepared by the precursor combustion method proposed in the present invention 0.2 Ce 0.7 Y 0.1 O 3-δ 、BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The particle size of the electrolyte powder is smaller and more uniform than that prepared by traditional methods, and is easier to sinter. Figure 3-4The SEM image of the electrolyte surface shows that the grains grow well without obvious secondary growth and present a closely connected polygonal structure with a density of more than 99%. The present invention proposes a precursor combustion method that couples the flame combustion synthesis method and the traditional sol-gel method to prepare a highly efficient sintered A-site Ba-containing proton conductor electrolyte BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY) and BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb) powder. The electrolyte powder can be sintered to a compact size (density > 99%) at 1300°C, which is much lower than the 1600°C sintering temperature required by the traditional method (comparative example). It breaks through the key bottleneck of the difficulty in sintering the A-site Ba-containing proton conductor electrolyte, and takes into account both battery performance and sintering temperature. The experimental method is simple and easy, the required raw materials are easy to obtain, and the energy consumption is greatly reduced. It has great industrial promotion value and provides strong support for the commercial application of SOFC.

[0088] The above shows and describes the basic process, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for efficiently preparing a Ba-containing proton conductor electrolyte at the A site by a precursor combustion method, characterized in that: The raw materials are weighed according to the stoichiometric ratio of the proton conductor electrolyte, the precursor liquid is prepared, the pH value of the precursor liquid is adjusted, the combustion conditions are controlled to heat and dry the precursor liquid, and the obtained powder is burned and calcined at high temperature to form a corresponding crystal structure.

2. The method for efficiently preparing a Ba-containing proton conductor electrolyte at the A-site by a precursor combustion method according to claim 1, characterized in that: The method comprises the following steps: S1: weigh the raw materials according to the stoichiometric ratio of the proton conductor electrolyte, dissolve them in distilled water, add citric acid and ethylene glycol to the resulting solution; adjust the pH value of the resulting solution to 7-8 until the flocs in the solution disappear, then place the resulting mixed solution at 40°C-60°C and stir, add NH4NO3 and H2O2 solutions, and stir and heat the resulting solution at 70°C-80°C for 8h-10h; S2: The precursor solution obtained in S1 is transferred into an evaporating dish, rapidly heated, continuously stirred, and dried into a porous solid material, and then the porous solid material is placed in a heat-insulating box filled with NO2 to cause violent combustion to obtain a white-yellow powder; S3: The obtained white-yellow powder is crushed, kept at 1000-1200° C. for 5-7 hours and cooled with the furnace to obtain an electrolyte powder that can be sintered efficiently.

3. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2, characterized in that: The proton conductor electrolyte includes BaCe x Y 1-x O 3-δ (BCY), BaZr x Y 1-x O 3-δ (BZY), BaZr x Ce y Y 1-x-y O 3-δ (BZCY) or BaZr x Ce y Y z Yb 1-x-y-z O 3-δ (BZCYYb), 0≤x+y+z≤1; The raw materials used are selected according to the stoichiometric ratio of the proton conductor electrolyte: Ba(NO3)2, Zr(NO3)4·5H2O, H8CeN8O 18 , Y(NO3)3·6H2O, Yb(NO3)3·5H2O.

4. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 3, characterized in that: Each raw material is H8CeN8O 18 , Zr(NO3)4·5H2O, Ba(NO3)2, Y(NO3)3·6H2O, Yb(NO3)3·5H2O are dissolved in distilled water in this order, among which H8CeN8O 18 As Ce source and combustion aid.

5. The method for efficiently preparing a Ba-containing proton conductor electrolyte at the A position by a precursor combustion method according to claim 2 or 3, characterized in that: In step S1, the molar ratio of metal cations to ethylene glycol and citric acid in the raw materials used for the proton conductor electrolyte is 1:1.5-2:1.5-2.

6. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2, characterized in that: The pH value of the solution is adjusted using ammonia water with a mass concentration of 15%-20%.

7. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2, characterized in that: The amount of NH4NO3 and H2O2 solution added is based on the proton conductor electrolyte, so that the molar ratio of the proton conductor electrolyte to the NH4NO3 and H2O2 solution is 1: (10-15): (5-10).

8. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2 or 7, characterized in that: The mass concentration of H2O2 solution is 60%-70%.

9. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2, characterized in that: In step S2, the evaporating dish containing the precursor solution is rapidly heated on an electric furnace at a heating power of 1000w-1500w and continuously stirred.

10. The method for efficiently preparing a proton-containing Ba-containing conductor electrolyte at the A-site by a precursor combustion method according to claim 2, characterized in that: The porous solid material is a black powder, which rapidly undergoes an exothermic reaction under the action of the combustion aids NH4NO3, NO2 and H2O2, and finally all the black powder burns violently, undergoes a phenomenon similar to the growth of tree branches, and transforms into a white-yellow powder.